2019
DOI: 10.22363/2312-8143-2019-20-2-134-139
|View full text |Cite
|
Sign up to set email alerts
|

Development of methodology for calculation of discontinuous circular welds in torsion

Abstract: The main criterion for the performance of welds is the strength. The least durable are the corner joints used to perform various types of welded joints. In the literature, the methods of calculating the strength of welded joints with solid seams are considered in sufficient detail. Methods of calculation of connection interrupted sutures absent. In this case, the greatest difficulty is the calculation of connections using circular intermittent seams, which are often performed in welded drums and pulleys. They … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…e number, arrangement, and interaction of defects can affect the thermal conductivity of carbon nanotubes. Studies have shown that the thermal conductivity of carbon nanotubes is generally contributed by two parts: the interaction between electrons and phonons and the interaction between phonons and phonons [19][20][21]. For carbon nanotubes, the interaction between phonons and phonons plays a major role in the entire heat conduction process; due to the large energy gap and low density of free carriers, the interaction between electrons and phonons makes little contribution to the thermal conduction process of carbon nanotubes [22].…”
Section: Molecular Dynamicsmentioning
confidence: 99%
“…e number, arrangement, and interaction of defects can affect the thermal conductivity of carbon nanotubes. Studies have shown that the thermal conductivity of carbon nanotubes is generally contributed by two parts: the interaction between electrons and phonons and the interaction between phonons and phonons [19][20][21]. For carbon nanotubes, the interaction between phonons and phonons plays a major role in the entire heat conduction process; due to the large energy gap and low density of free carriers, the interaction between electrons and phonons makes little contribution to the thermal conduction process of carbon nanotubes [22].…”
Section: Molecular Dynamicsmentioning
confidence: 99%